FRI0016 MUTATIONAL LANDSCAPE OF MYELODYSPLASTIC SYNDROME IN PATIENTS WITH AUTOIMMUNE RHEUMATOLOGICAL DISORDERS. (June 2019) - Hong, Lih En; Singhal, Deepak; Wee, Amilia; Chhetri, Rakchha; Kutyna, Monika; Wechalekar, Mihir; Hiwase, Devendra; Proudman, Susanna
Abstract : Background: Autoimmune rheumatological disorders (AIRD) have been described in myelodysplastic syndrome (MDS) and related-myeloid disorders but its association remains unclear. Immunosuppressive treatment of AIRD could cause therapy-related myeloid neoplasm (t-MN) or confound the secondary diagnosis of MDS. The prevalence of cytopenia in patients with AIRD is unknown and the mutation profile of patients with AIRD and concomitant MDS have not been well characterised. Objectives: This study aims to evaluate the prevalence of cytopenia in AIRD and analyse the mutation profile of patients with concomitant diagnosis of AIRD and MDS by interrogating the databases of 2 large institutions - Royal Adelaide Hospital Rheumatology Department (RAH-RD) and South Australia-Myelodysplastic Syndrome (SA-MDS). Methods: Demographic, clinical, laboratory and treatment data of 2663 patients from RAH-RD and 1157 patients from SA-MDS were analysed according to the idiopathic cytopenia of undetermined significance (ICUS) criteria. Patients with persistent cytopenia (>6 months) were defined as follows: haemoglobin <100g/L, absolute neutrophil count <1.8x10 9 /L and platelet <100x10 9 /L. Within the SA-MDS registry, 237 bone marrow samples were analysed for 43 myeloid neoplasms associated genes and 20 Fanconi (FA) DNA repair pathway genes with targeted massively parallel sequencing. An in-house filtering pipeline was used to identify somatic mutations. Results: Within RAH-RD database, 79 patients (3%) fulfilled the criteria for at least 1 cytopenia. 21 patients underwent bone marrow biopsy, with 9 bone marrow samples being diagnostic of MDS. Neutropenia was most common (27/79 patients, 34%), followed by anaemia (20/79 patients, 25%) and thrombocytopenia (6/79 patients, 8%). Within SA-MDS database, 62 patients (5%) had concomitant AIRD. Rheumatoid arthritis is the most common AIRD diagnosis (21/62 patients, 34%) in the SA-MDS database. Combined analysis of both databases revealed that 71/3820 patients (1.9%) had a concomitant diagnosis of both AIRD and MDS. The cytogenetic and mutational profile of patients with concomitant diagnosis of AIRD and MDS within the SA-MDS database were analysed and 56 mutations were discovered in this group. Mutation in ASXL1 was the most common (6/20 patients, 30%), followed by TET2 (5/20 patients, 25%) and lastly TP53 (4/20 patients, 20%). There is significantly higher frequency of IDH1 mutation in the AIRD-MDS cohort compared to patients with MDS only. Three patients with TP53 mutation developed MDS following treatment for AIRD (therapy-related MDS). Conclusion: In a large cohort of patients with AIRD, 3% of patients developed ongoing cytopenia and 0.3% were diagnosed with MDS. This finding is higher than the incidence of MDS in the general population (0.03-0.05%). Within the SA-MDS registry, 5% of patients had concomitant diagnosis of AIRD. Our findings warrant further study and have potential implications for selection of disease-modifying drugs for patients with AIRD. References: [1] Mekinian, A, et al. (2015). Systemic inflammatory and autoimmune manifestations associated with myelodysplastic syndromes and chronic myelomonocytic leukaemia: a French multicentre retrospective study. Rheumatology, 55(2), 291-300. Disclosure of Interests: Lih En Hong: None declared, Deepak Singhal: None declared, Amilia Wee: None declared, Rakchha Chhetri: None declared, Monika Kutyna: None declared, Mihir Wechalekar Grant/research support from: Janssen & Janssen Philadelphia USA, Devendra Hiwase Grant/research support from: Novartis, Susanna Proudman Grant/research support from: Actelion, GSK, Consultant for: Actelion, Boehringer-Ingelheim, Speakers bureau: Actelion